Fort Aubrey, Hamilton County - Ivey, Darren L. (Kansas State University, The Chapman Center for Rural Studies, 2015)
This study examines Fort Aubrey, a Civil War-era frontier post in Syracuse Township, Hamilton County, and the men who served there. The findings are based upon government and archival documents, newspaper and magazine articles, personal reminiscences, and numerous survey works written on the subjects of the United States Army and the American frontier.
Darren L. Ivey, “Fort Aubrey, Hamilton County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/158.
Keywords: Aubrey's Crossing; Darren Ivey; Edward Wanshear Wynkoop; Fort Aubrey; Glorieta Pass; Fort Zarah